PENTINGNYA MEMAHAMI PERBUATAN HUKUM TELEKOMUNIKASI DALAM KERJASAMA ANTARA PT. IM2 DENGAN PT. INDOSAT - Harsono, Nonot (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
There is a difference between regulatory opinion of the Telecommunications Regulator/Ministry of Communications with the Corruption Court Judge on act did by PT. IM2 in collaboration with PT. Indosat. Title of cooperation between this service providers and network operators are